2016
DOI: 10.1016/j.bbrc.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of gene expression in response to cold stress in diverse rice genotypes

Abstract: Cold stress is a major factor affecting rice (Oryza sativa) growth and productivity, limiting its distribution worldwide. Rice production is affected primarily due to its vulnerability to cold stress at seedling stage, as well as reproductive stage leading to spikelet sterility. We report here the analysis of 21 diverse rice genotypes from the USDA mini-core collection for cold tolerance and categorized their tolerance levels on the basis of reduction in growth measured by root and shoot length. The screening … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Lipid transfer proteins (LTPs) play an important role in abiotic stress tolerance [89], and can facilitate the inter-membrane exchange and transfer of various amphiphilic molecules including phospholipids, glycolipids, steroids, acyl-CoAs, and fatty acids [90]. Transcript levels of LTPs increased in response to drought [91], salt [92] and cold [93] and the increase of non-specific lipid-transfer protein 1 expression in tolerant genotypes give more support to its role of increasing tolerance to abiotic stress.…”
Section: Resultsmentioning
confidence: 99%
“…Lipid transfer proteins (LTPs) play an important role in abiotic stress tolerance [89], and can facilitate the inter-membrane exchange and transfer of various amphiphilic molecules including phospholipids, glycolipids, steroids, acyl-CoAs, and fatty acids [90]. Transcript levels of LTPs increased in response to drought [91], salt [92] and cold [93] and the increase of non-specific lipid-transfer protein 1 expression in tolerant genotypes give more support to its role of increasing tolerance to abiotic stress.…”
Section: Resultsmentioning
confidence: 99%
“…31 Previously, it was shown that LTPs are differentially expressed in response to cold stress in different rice genotypes. 22,27 Therefore, the role of LTPs was further investigated in response to low-temperature stress, for four rice genotypes in different tissues (flag leaf and inflorescence). The OsLTP7, OsLTP8, OsLTP10, OsLTP12, OsLTP14 and OsLTP25 genes are differentially expressed in different tissues in response to cold stress (Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Rice genotypes Nipponbare (tolerant), M202 (tolerant), Cypress (sensitive) and Secano do Brazil (sensitive) were selected based on data collected from a previous screening experiment. 22 Seed were germinated and individual seedlings transplanted into 500 ml plastic pots, containing commercial potting soil substrate (Redi Earth). All genotypes were grown in the greenhouse (26/22°C ± 1°C with a photon flux density of 600 μmol −2 s −1 , light/dark cycle of 14/10 h), and the pots placed in trays full of water simulating flooded conditions.…”
Section: Reproductive Stage Cold Stress Treatmentmentioning
confidence: 99%
See 2 more Smart Citations